Leverage, Arus Kas Operasi, Ukuran Perusahaan, Intensitas Aset Tetap dan Revaluasi Aset Tetap - Resti Yulistia M; Nurul Dwi Septiyani; Arie Frinola Minovia; Yunilma Yunilma (Universitas Negeri Padang, 2021)
Since Indonesian accounting standards allow companies to choose between cost model and revaluation model on their fixed asset, there are still few companies that revalued their assets. This study examines what factors make banking companies choose to revaluate fixed asset, that are contracting factors (leverage, operating cash flow), political factors (firm size) and asymmetry information (intensity of fixed assets). By using logistic regression, the result of this study showed that firm size and fixed asset intensity had a positive effect on the company choice to revaluate fixed assets, while leverage had a negative effect on fixed asset revaluation. This study support early research with regard to contracting, political cost and asymmetry information. This study failed to find the effect of operating cash flow on fixed asset revaluation. Based on the results of this study, banks should consider leverage, company size and the intensity of fixed assets more than cash flow when choosing to revaluate fixed assets. Keywords: Leverage; Operating Cash Flow; Size Firm; Fixed Asset Intensity; Fixed Asset Revaluation